INTEGRASI MENUJU INDUSTRI KREATIF YANG KUAT DAN DINAMIS - Anjaningrum, Widiya Dewi (LP2M Institut Teknologi dan Bisnis Asia Malang, 2021)
The purposes of this study are to determine the direct and indirect effects of market and entrepreneurial orientation on competitive advantage through dynamic capabilities and to prove the role of dynamic capabilities as an intervening variable. This research is a field research study on creative industries in Malang, Indonesia. A sample of 100 respondents was selected by accidental sampling technique. Data was obtained through questionnaire survey and processed with Partial Least Square analysis. The results showed that market and entrepreneurial orientation had a positive and significant direct effect on competitive advantage, it also had a indirectly effect through dynamic capabilities, and dynamic capabilities consisting is not able enough to mediate market and entrepreneurial orientation on the competitive advantage. An integration of market and entrepreneurial orientation to create high dynamic capabilities and strong competitive advantage is a must for creative industries. To become a strong industry that has high dynamic capabilities to compete, the creative industries should increase information acquisition so that products are more in line with customer expectations.